The Impact of Leadership with Love on Job Loyalty among Workers in the Health Sector in Hafr Al-Batin Governorate (International Journal of Financial, Administrative and Economic Sciences, 2024)
This study aimed to determine the extent of the impact of the leadership style with love on the performance of the organization in general. It also shed light on leadership with love (fatherly leadership) or as leadership with the maternal nature is called, as an effective leadership style, and an attempt to show and clarify its role in improving the job satisfaction of subordinates, through... Reviewing many relevant studies, and for this purpose, the researcher used the questionnaire tool in order to reach the objectives of the study. The results showed that leadership with love was high in the case of the study, as it came with an average of (3.89). The study finally concluded that love is an effective leadership method for achieving job satisfaction. The percentage of influence of leadership with love on job loyalty reaches 56%, and the results confirm the validity of the regression model, as it was statistically significant, the value (F) = 459.124, the value of the level of significance is less than 0.001, and the value of the regression coefficient = 0.574, which shows that the more leadership with love increases by  One, job loyalty increased by 0.574, and the regression coefficient was also statistically significant, as the value of (t) = 21.427, and the significance level value was less than 0.05.
Keywords: Leadership with Love; Job Loyalty